Phospholipid fraction has protective effect by improving inflammation and skin barrier function in ischemia-reperfusion injury in mice. Issue 1 (1st January 2020) - Kim, Su-Young; Kim, Yu-jin; Lee, Esther; Choi, Seong Hyun; Moon, Jeong Su; An, Hyo Sil; Ji, Eun Su; Na, Jungtae; Kim, Beom Joon
ABSTRACT: The total phospholipid fraction (TPF) has anti-inflammatory properties and reduces apoptosis in animal models. Our objective was to assess the effects of TPF on pressure ulcers in a mouse model of cutaneous ischemic-reperfusion (I/R) injury. Cutaneous I/R injury was created by trapping the dorsal skin between two magnetic disks for 12 h, followed by disk removal. TPF administration in I/R areas at the beginning of reperfusion significantly inhibited the formation of pressure ulcers. The number of neutrophils and M1 macrophages and the levels of proinflammatory mediators MCP-1, IL-1β, IL-6, and TNF-α in the wound area were reduced upon TPF treatment. Collagen synthesis and α-SMA-positive microvessel density significantly increased in the wounds of TPF-treated mice. Additionally, TPF inhibited cutaneous I/R injury-induced formation and accumulation of apoptotic cells. Moreover, TPF increased the expression of filaggrin and involucrin. In conclusion, TPF may inhibit cutaneous I/R injury-induced formation of pressure ulcers by regulating inflammation, collagen production, angiogenesis, and skin barrier restoration. Therefore, exogenous application of TPF might have therapeutic potential with respect to cutaneous I/R injuries like decubitus ulcers.